Heterogeneity in Short‐Term Suicidal Ideation Trajectories: Predictors of and Projections to Suicidal Behavior. Issue 3 (25th June 2018) - Allan, Nicholas P.; Gros, Daniel F.; Lancaster, Cynthia L.; Saulnier, Kevin G.; Stecker, Tracy
Abstract : Objective: Little is known about suicidal ideation stability, including whether stability is heterogeneous or homogeneous between individuals. Studies of this kind are necessary to understand the progression from suicidal ideation to action. Method: This study examined suicidal ideation trajectories, using growth mixture modeling, in a sample of 359 past/current military service members ( M age = 32.1 years, SD = 7.7; 88.3% male). Self‐reported suicidal ideation information was collected at baseline and follow‐up sessions at months 1, 3, 6, and 12. Following extraction of the best‐fitting solution, predictors of trajectory status were examined and trajectory status was used to predict suicidal behavior between baseline and month 12 assessments. Results: Results revealed four trajectories, Low‐Stable ( n = 125), Moderate‐Stable ( n = 101), High‐Stable ( n = 76), and High‐Rapidly Declining ( n = 57). In general, the High‐Stable trajectory had the highest levels of perceived burdensomeness, thwarted belongingness, PTSD symptoms, and drug use. The High‐ and Moderate‐Stable trajectories had the highest rates of suicidal behavior between baseline and month 12. Conclusions: Suicidal ideation, even in individuals with elevated ideation, is not a homogeneous construct over time. Stability of suicidal ideation might be an important risk factor, even if ideation is only moderately elevated.